Dielectric Rod Waveguide Antenna as THz Emitter for Photomixing Devices - Rivera-Lavado, Alejandro; Preu, Sascha; García Muñoz, Luis Enrique; Generalov, Andrey; Montero-de-Paz, Javier; Doehler, Gottfried; Lioubtchenko, Dmitri; Mendez-Aller, Mario; Sedlmeir, Florian; Schneidereit, Martin; Schwefel, Harald G. L.; Malzer, Stefan; et al. (IEEE Transactions on Antennas and Propagation, 2015)
We propose a dielectric rod waveguide antenna (DRW) integrated with a photomixer as a THz emitter. This represents a different approach as opposed to the classical solution of a substrate lens. Main goals are an inexpensive alternative to substrate lenses, reduction of both reflections on the semiconductor-air interface and scattering of terahertz-generated power into the substrate. A radiation pattern measured at 137 GHz is shown as a proof-of-concept. In order to increase radiated power, the improvement of the rod antenna is discussed. Finally, as an application example, evanescent coupling of the DRW into a high index whispering gallery mode resonator is shown.
Keywords: Dielectric rod waveguide (DRW) antenna; integrated emitter; photomixer; THz antenna; whispering gallery mode resonators